Prospects of Employing Graduates of Computer Science and Technology Diploma Programs in Asir Region, Saudi Arabia: An Analysis for the Period 2019-2023 - Sabah Abdellatif Hassan Ahmed (International Journal of Computers and Informatics, 2024)
This paper aims to explore and analyze the employment processes of graduates from computer science diploma programs in Saudi Arabia during the period from 2020 to 2023. This paper employed a quantitative research approach and utilize the survey method to collect data. The survey instrument designed to address the research objectives and questions outlined earlier. The collected survey data was analyzed using the Statistical Package for the Social Sciences (SPSS) software. The target population for this study comprises all graduates of computer science and technology diploma programs in the Asir Region of Saudi Arabia for the period from 2019 to 2023. Since it is not feasible to survey the entire population, a representative sample of 60 participants had been selected using a random sampling technique. The results indicate that there are 42 (70%) who are Employed, there are 10 (16.7%) who are Self-Employed, and there are only 8 (13.3%) who are Unemployed. Which indicates that Graduates of Computer Science and Technology Diploma Programs in Asir Region, Saudi Arabia have higher probabilities to be employed. There are 19 (31.7%) who were graduated in 2019 and 2020, and there are 10 (16.7%) who were graduated in 2022. While there are 9 (15%) who were graduated in 2023. And there are only 3 (5%) who were graduated in 2021. there are 26 (43.3%) who are Employed in Public Sector, there are 20 (33.3%) who are Employed in private Sector, there are 6 (10%) who are Employed in mixed Sector (public and private), and there are only 8 (13.3%) who are Unemployed. Which indicates that private sector faces greater challenges in employing computer science program graduates compared to the public sector.